LETHAL CONCENTRATION 50% (LC)-50 DAN PATOGENESITAS ISOLAT Aeromonas salmonicida PADA IKAN Cyprinus carpio - Riza Priyatna; Sudarmanto Indarjulianto; . Kurniasih (Jurnal Sain Veteriner, 2011)
Aeromonas salmonicida is the bacterial agent of furunculosis in fish causing economical loss in the fresh water aquaculture. The objective of this current study was to reveal the lethal concentration 50% (LC 50) andpatogenecity of four different isolates of this organism originated from different location in Indonesia. All isolates were inoculatedo n TSA prior to identification and characterization. The LC-50 of each isolatew asevaluated in fish.The result concluded that four isolates were atypical, the same as A. salmonicida from ATCC. The higher dose of A. salmonicida caused a higher mortality of fish within a shorter time of contact. The value of LC-50 was 3,55x 10' cel/ml to 2,75 x l0o cell/ml. This species caused septicaemia, hemorrhage, necrosis, and ulcer. The gill, liver, ren, and spleen, exhibited congestion, necrosis, and inflammation.Keywords: Aeromona salmonicida, LC-50